Sympathetic and Catecholaminergic Alterations in Sleep Apnea with Particular Emphasis on Children - Hakim, Fahed; Gozal, David; Gozal, Leila K. (Frontiers in Neurology, 2012)
Sleep is involved in the regulation of major organ functions in the human body, and disruption of sleep potentially can elicit organ dysfunction. Obstructive sleep apnea (OSA) is the most prevalent sleep disorder of breathing in adults and children, and its manifestations reflect the interactions between intermittent hypoxia (IH), intermittent hypercapnia, increased intra-thoracic pressure swings, and sleep fragmentation, as elicited by the episodic changes in upper airway resistance during sleep. The sympathetic nervous system is an important modulator of the cardiovascular, immune, endocrine and metabolic systems, and alterations in autonomic activity may lead to metabolic imbalance and organ dysfunction. Here we review how OSA and its constitutive components can lead to perturbation of the autonomic nervous system in general, and to altered regulation of catecholamines, both of which then playing an important role in some of the mechanisms underlying OSA-induced morbidities.